Rapid one-step cleanup method to minimize matrix effects for residue analysis of alkaline pesticides in tea using liquid chromatography–high resolution mass spectrometry. (30th November 2019) - Hu, Shuping; Zhao, Min; Mao, Qiqi; Fang, Chengyan; Chen, Dawei; Yan, Pengcheng
Highlights: Rapid one-step cleanup method to minimize matrix effects for pesticides in tea. Removal of caffeine and polyphenols were achieved by PCX-based DSPE procedure. Weak absolute matrix effect and low relative matrix effect were achieved. LC–HRMS with pre-column dilution injection was used to overcome solvent effects. This method was validated and applied to the alkaline pesticides analysis in tea. Abstract: Matrix effects in complex tea matrices remains a great challenge to rapid quantitative analysis of multi-residue pesticides by analysis of mass spectrometry. Herein, a mixed-mode polymer cationic exchange based dispersive solid-phase extraction (DSPE) procedure was established to eliminate matrix effects of tea for a rapid target alkaline multi-residue pesticides analysis. One-step DSPE procedure can eliminate matrix interferences from the tea extract without additional dilution or tedious cleanup operations. Liquid chromatography–high resolution mass spectrometry using pre-column dilution injection mode was used as the detection technique, while eliminating solvent effects of target analytes and improving the detection sensitivity. Based on this effective analytical method, the results of absolute matrix effects were within 0.77–1.08 for quantitation of the 68 alkaline pesticides, and superior relative matrix effects were also achieved with RSD values below 9.8%. Finally, this method was validated and applied to the alkaline pesticides analysis of the 123 tea samples.